Handbook of concentrator photovoltaic technology - Algora, Carlos; Rey-Stolle, Ignacio (John Wiley & Sons Inc., 2016)
Concentrator Photovoltaics (CPV) is one of the most promising technologies to produce solar electricity at competitive prices. High performing CPV systems with efficiencies well over 30% and multi-megawatt CPV plants are now a reality.